First dietary study of the critically endangered black morph Bornean banded langur (Presbytis chrysomelas chrysomelas) using DNA metabarcoding - Mohammad Noor-Faezah; Abd Rahman Mohd-Ridwan; Nur-Aizatul Tukiman; Roberta Chaya Tawie Tingga; Mohamad Fhaizal Mohamad Bukhori; Badrul Munir Md-Zain (Biodiversity Data Journal)
The black morph Bornean banded langur (Presbytis chrysomelas chrysomelas) is a critically endangered primate endemic to Sarawak, Borneo. Detailed knowledge of its diet is essential for guiding effective conservation strategies. This study employed DNA metabarcoding, targeting the chloroplast trnL region to characterise the dietary composition of P. c. chrysomelas. Faecal DNA from three individuals was extracted, amplified and sequenced using next-generation sequencing. Results identified 28 unique amplicon sequence variants corresponding to nine plant species spanning nine genera and eight families. The most abundant plant families were Euphorbiaceae and Achariaceae, with Elateriospermum and Hydnocarpus as dominant genera. At the species level, Elateriospermum tapos and Hydnocarpus anthelminthicus were the primary food sources. This study represents the first DNA metabarcoding-based dietary analysis of P. c. chrysomelas, providing valuable insights into its feeding ecology. These findings will support targeted conservation efforts, particularly within Tanjung Datu National Park, Sarawak.